The safety, efficacy, and functional outcomes on arthroscopic fixation of posterior cruciate ligament avulsion fracture by a bio-absorbable anchor or traditional pull-out technique: A prospective cohort study - Ren, Xiangyu; Wang, Jianing; Yang, Shulong; Liu, Zhe; Wang, Tianda; Zhang, Teng; Li, Haoxin; Zhang, Zhong (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The posterior cruciate ligament avulsion fracture (PCLAF) is a special type of PCL rupture, and arthroscopic fixation for PCLAF has been recommended currently. The bio-absorbable suture anchor is a novel internal fixation for PCLAF. This study aims to estimate and compare the safety, efficacy, and functional outcomes between the bio-absorbable anchor and the traditional suture pull-out technique for arthroscopic fixation of PCLAF. Methods: This was a prospective case-control study. PCLAF patients were included from January 1, 2020, to August 31, 2021, in our department, and randomly divided into the absorbable anchor group and control group (pull-out suture fixation). Clinical assessments included: post drawer test, gravity test, anterior-posterior laxity (KT-2000), range of motion, Lysholm and International Knee Documentation Committee (IKDC) scores, total failure rate, and returning to sports rate. The minimum follow-up was 1 year (y). Results: 31 patients had accomplished the 1y follow-up (missing rate: 13.9%). We did not face any complications such as neurovascular injury, fever, infection, un-union, or re-rupture during the follow-up. CT scan showed that all of the patients in the two groups had a well bone union at 3 months in post-operation. At 1y follow-up, the total failure rate of the bio-absorbable anchor group (1/17, P =0.036) was lower than the control group (5/14), and the IKDC (86.24±4.35, P =0.008) and return to sports rate (11/17, P =0.045) of the bio-absorbable anchor group were higher than that of the control group (81.43±5.06) (4/14). Conclusion: Both the bio-absorbable anchor and suture pull-out technique for arthroscopic fixation of PCLAF have acquired a well bone union and superior safety, but the bio-absorbable anchor group had better efficacy and functional outcomes than the traditional pull-out technique. Level of Evidence: Level 2.